Application of the C4.5 Algorithm to Predict the Effectiveness of Google Adwords Ads - Aditya Gusti; Sri Hadianti (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Google Adswords is a product that you can use to promote your business, help sell products or services, raise awareness, and increase traffic to your site. Nayaka Technology is currently using the services of Google Adswords as a way to boost sales and expand the network. However, because broadcast planning was not carried out in advance, the results obtained were not satisfactory. In the next campaign, planning will be carried out first using the history on the previous campaign's broadcast reports, the data is processed using data mining techniques to predict the market. The model used is the C4.5 algorithm, the results of the C4.5 algorithm model are tested using a confusion matrix and get 92.70% of accuracy, 78.23% of precision and 97.25% of recall.Keywords: Google Adswords, Algoritma C4.5, Data Mining.